Phosphite mediated molecular editing via switch to meta-C-H alkylation of isoquinolines: emergence of a distinct photochemical [1,3] N to C rearrangement - Rani, Soniya; Ray, Anuj Kumar; Dewangan, Devendra Kumar; Patil, Nita Aruna Ramchandra; Aarthika, M.; Paul, Ankan; Maity, Pradip (Chemical Science, 2025)
The isoquinoline core is present in one of the largest subsets of bioactive natural products. The multifunctional isoquinoline core exerts diverse bioactivity, resulting in the development of numerous isoquinoline-based drugs and molecules that are currently under clinical trials. We developed a new approach for phosphite-mediated [1,2] alkyl migration for an overall ortho-C-H alkylation via N-alkylation of isoquinoline. Tuning the phosphite-mediated protocol to switch the site selectivity would expedite direct and diverse multi-C-H bond functionalization. We report a new approach starting with a simple N-alkylation of isoquinoline with sterically and electronically diverse alkyl bromides for their phosphite-mediated photochemical [1,3] N to C rearrangement followed by a rearomatization sequence that leads to meta-C-H (C4) alkylation. Combined experimental and computational studies unveiled the emergence of an unprecedented C-N bond cleavage pathway from the singlet excited state of the enamine-type intermediate. Our radical bond-cleavage pathway favors substituted alkyl group migration that complements the recently successful meta-alkylation methods with smaller and more reactive electrophiles. This switch in site selectivity via tuning the phosphite-mediated protocol resulted in sequential C-H difunctionalization of isoquinoline including regiodivergent ortho, meta-dialkylations of isoquinolines.